Pengembangan dan Evaluasi Usability Website Pemasaran Alat Hadroh Menggunakan System Usability Scale (SUS) - Akhmad Fadjeri; Danu Dwi Setiawan (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2026)
The rapid growth of digital technology has encouraged micro, small, and medium enterprises (MSMEs) to adopt digital marketing strategies in order to remain competitive. This study aims to develop a marketing website for the Syekh Hadroh MSME and to evaluate the quality of the developed system in terms of functionality and usability. The research employed a Research and Development (R&D) approach with the Waterfall model as the system development method. Functional testing was conducted using Black Box Testing with the Equivalence Partitioning technique, while usability evaluation was performed using the System Usability Scale (SUS) involving 10 respondents. The results of Black Box testing indicate that all test scenarios were successfully executed with a success rate of 100%, demonstrating that the system functions according to the specified requirements. Furthermore, the SUS evaluation produced an average score of 73, which falls into the “good” usability category, indicating that the system is easy to use and well accepted by users. These results suggest that the developed marketing website is functionally reliable and usable, and therefore suitable for implementation as a digital marketing medium to support market expansion and improve service quality for MSMEs.